Influence of different factors in the growth of endophytic bacteria of sugarcane - Lester González Rodríguez; Heydrich Mayra; Anar Janet Rodríguez Cheang; Marcia M. Rojas Badía (Revista Colombiana de Biotecnología, 2015)
Among the efforts done in Cuba to the sustainability in the agricultural system, one of them is the use of bioproducts, which have a relevant economic, ecological and social impact. The sugarcane is one of main crops in our country and it has a great importance at world level. In the present work is demonstrated the effect of different carbon and nitrogen sources in the growth of 5 entophytic bacteria (three of Gluconacetobacter diazotrophicus, one of Bacillus licheniformis and one ofEnterobacter agglomerans) were demonstrated. As the same form are studied the influence of juices from five varieties, as well as, different concentrations of fitohormones indole3acetic acid and giberelic acid on the growth. Was demonstrated that asparagine and ammonium sulfate as nitrogen sources added to LGI medium enhance the growth a major growth of the studied endophytic bacteria. The LGI medium supplied with juices of sugarcane enhance the growth of microorganisms (p≤0,05) and don't exist any relationships among the origin of the juice and the strains. On the other hand, the fitohormones at low concentrations don't affect the growth but at high levels of these hormones inhibit the growth. It's necessary to study the factors that have influence on the interaction between the plant and endophytes to use their potentialities as plant growth promoters.